Changes in the land use and coverage in the PPAs of the rivers from the County of Jacarezinho-PR, from 1995 to 2015 - Motta Abrantes, Angelica Scheffer da [UNESP]; Piroli, Edson Luis [UNESP] (Univ Estadual Centro-oeste, 2017)
The research aimed to analyze the changes in the land use and coverage in the permanent preservation areas of the rivers from the County of Jacarezinho-PR, from 1995 to 2015, and then confront the results with the current legislation. To its development, it was elaborated databases and thematic maps of land use and coverage, due to remote sensing products and geoprocessing techniques. Thus, the generated maps from the supervised classification allowed identifying four classes of land use and covering in the permanent preservation areas: temporary culture, forest area, forestry and pasture. It was concluded that the images obtained by the TM sensor of Landsat 5 and by the sensor OLI of the Landsat 8 allowed the mapping of the area and provided, through geoprocessing techniques, a database for the supervised classification of land use and coverage and for future planning. Also, it was verified that the permanent preservation areas of the county are not in conformity with the new Forest Code.
Keywords: Forest Code; remote sensing; land use; geoprocessing